Logistics Management Security Practices: A Quantitative Analysis of Procedural Inventory Security Practices - Kabinga, Lawrence Kabuthi (Logistics Management Inventory Security Practices, Edition 1, 2025)
Warehousing security is an emerging trend which is shaping the performance of logistics companies and ensuring a smooth supply chain flow. Several factors can interrupt the smooth flow of materials along the logistics cycle increasing risks and reducing customer satisfaction. To this end, this book chapter explores the effect of inventory security procedural practices on the security of inventory held by logistics service provider companies in Nairobi County. A descriptive research design was used as the research design. The target population of the study was composed of 583 employees of clearing and forwarding companies. The convenient sample size of the study was 175 employees of clearing and forwarding companies in Nairobi County, Kenya, which accounted for 30% of the target population. The convenient sampling method was used to target organizations with close proximity and convenience to the researcher saving time and money. Questionnaires were administered to warehouse employees for primary data collection. Simple frequency count and percentage for the demographic information and introduction sections of the study, followed by descriptive statistics and inferential statistics were used to analyze the data collected from the questionnaires. Descriptive statistics included mean, median and standard deviation. Inferential statistics included correlation and regression analysis which were done through SPSS. The book findings indicate that the results indicate a moderately strong relationship between the dependent variable (organizational logistical services performance) and the independent variable (inventory security procedural practices) by clearing and forwarding companies in Nairobi County (r = 0.47** p value = 0.000). This implies that the above relationship was significant because the p value 0.000 was less than 0.05 (significant level). Secondly, inventory security procedural practices have a significant difference in the overall mean of organizational logistical services performance (F = 4.87, p < 0.05). Therefore, inventory security procedural practices had a profound effect on the overall mean of organizational logistical services performance. A multiple coefficient of variation (R) value of 0.47 indicates a high and positive relationship between the dependent variable (organizational logistical services performance) and the independent variable (inventory security procedural practices). According to the R-Square value of 22 percent record-keeping practices, computerized stock documentation and stock marking activity explained 22 percent of variations in organizational logistical services performance by clearing and forwarding companies in Nairobi County. In the region of Kenya, random error or other factors account for 60.4 percent of those variations. In conclusion, as we move towards green suitable practices in the logistics sector, we should conduct further research on the potential contribution of environmental design activity. These green security initiatives can be used to reduce the environmental impact caused by other security measures that are more hazardous to the environment.